2008
DOI: 10.1007/s12031-008-9149-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Cerebral Endothelial Cells Activated by Glutamate/MK-801: Significance in Ischemic Stroke Injury

Abstract: Glutamate is a major excitatory neurotransmitter in the central nervous system and plays a significant role in the pathophysiology of ischemic stroke. During acute ischemic cerebrovascular disease, glutamate efflux in the CNS produces excitotoxicity in neurons and may mediate forms of stress in other tissues expressing glutamate ionotropic (N-methyl-D-aspartate (NMDA)) receptors, e.g., cerebral endothelial cells. While endothelial cell stress in response to glutamate has been reported (oxidant stress, loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Recently, deleterious effects of homocysteine onto the BBB were reported to be mediated by NMDAR [2]. Furthermore, we and others were able to show that MK801 alone can affect the proteome and the intracellular Ca-level of BBB models [16,17]. Consequently, it should be taken into consideration that currently unknown serum components may act as NMDAR agonists or that MK801 can affect the intracellular Ca-level without prior NMDAR stimulation which can lead to decreased ROS formation and subsequent lower glucose transporter functionality.…”
Section: Resultsmentioning
confidence: 53%
“…Recently, deleterious effects of homocysteine onto the BBB were reported to be mediated by NMDAR [2]. Furthermore, we and others were able to show that MK801 alone can affect the proteome and the intracellular Ca-level of BBB models [16,17]. Consequently, it should be taken into consideration that currently unknown serum components may act as NMDAR agonists or that MK801 can affect the intracellular Ca-level without prior NMDAR stimulation which can lead to decreased ROS formation and subsequent lower glucose transporter functionality.…”
Section: Resultsmentioning
confidence: 53%
“…These effects involve MMP (ADAM) secretions. 8,39 Few studies have reported brain vascular proteome data, and most focus on BBB function after insults, 40 or are based on cultured brain microvascular ECs. 41,42 This present study focuses on the physiological patterns of at-risk stages for bleeding and constitutive elements involved in fMV cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of presumably GluN1/GluN2C NMDAR with glutamate in the presence of D‐serine and endothelial nitric oxide synthase leads to vasodilation (LeMaistre et al, 2012). Activation of endothelial NMDAR has been reported to impair blood–brain barrier function and to play a role in ischemia and edema (Minagar et al, ).…”
Section: Discussionmentioning
confidence: 99%